The Effect Of My Therapy Digital Application On Medication Compliance In Tuberculosis Patients - Irene Dapakuri; Sarlina Luma; Oklan Liunokas; Domianus Namuwali; Pius Selasa (Poltekkes Kemenkes Kupang, 2025)
Tuberculosis (TB) remains a major health problem in Indonesia, including at Puskesmas Oesapa in Kupang City. One of the challenges in TB treatment is the low adherence of patients in routinely consuming Anti-Tuberculosis Drugs (OAT). The use of a digital application such as My Therapy is expected to help patients remember their medication schedules and monitor their adherence. The objective is to analyze the effect of using the My Therapy digital application on medication adherence among Tuberculosis patients at Puskesmas Oesapa, Kota Kupang. This study used a quasi-experimental design with a one-group pre-test and post- test approach. The sample consisted of 47 Tuberculosis patients who were selected through purposive sampling based on inclusion criteria. Data was collected using the Morisky Medication Adherence Scale (MMAS-8) questionnaire. Bivariate analysis was performed using the Wilcoxon Signed- Rank Test because the data was not normally distributed. The results showed that the average medication adherence score increased after the intervention using the My Therapy application. The Wilcoxon test yielded a p-value of 0.000, indicating a significant difference in adherence levels before and after the intervention. Conclusion: The use of the My Therapy digital application is effective in improving medication adherence among Tuberculosis patients at Puskesmas Oesapa, Kota Kupang. This application is expected to be a supportive innovation in efforts to control TB in then community.